KEJAHATAN PENCUCIAN UANG DALAM PERSPEKTIF FIQH JINAYAH - Shofi Salsabilla; Arum Fadilah Wati; Muti’ah Muti’ah (Al-Ittihad: Jurnal Pemikiran dan Hukum Islam, 2023)
As time progresses, technology becomes more advanced, along with that progress does not always have a positive impact on the world and society, in fact sometimes crime is increasingly rampant as well. In the case of money laundering, for example, it is one of the results of the influence of the times, briefly money laundering can be understood to get money from a crime which is then processed in such a way that it looks like clean or holy money again so that it can be used by unscrupulous persons. irresponsible consumer. In this scientific article, the author will briefly analyze the discussion about money laundering or also known as money laundering from the perspective of criminal law as well as the perspective of fiqh jinayah in Islam